Analisa Tegangan Sentuh Dan Tegangan Langkah Di Gardu Induk 150 KV Batu Besar Menggunakan Sistem Grid - Wahyu Zarniadi; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Generally, the electrical fault that occurs at substations forms a phase-to-ground short circuit fault. The fault currents flowing on the earthing grid can different result in voltage gradients at the ground level around the substation. The purpose of this study to evaluate the earthing system at the substation of Batu Besar, and to find out whether grid earth resistance meets standards. Then, to protect people who walk or touch equipment of electric shock. The earthing system needs to be evaluated in each period to get the touch voltage and step voltage that conforms to safety and security standards. This research method is to collect parameters ρ, ρs, hs, A, LT, and h, which are calculated using the formula of grid earth resistance, touch voltage, and step voltage. Later the results of calculations, analysis, and compare using the IEEE Std 80-2013 standard. Based on the analysis results obtained grid earthing resistance of 0.62 Ω, touch voltage of 737.65 V and step voltage of 2458.43 V. The results of the earthing system evaluation at the substation of Batu Besar meet the standards of IEEE Std 80-2013.Keyword : grid earthing system, touch voltage, step voltage